Ultrasound-Guided Neuraxial Precision in a High-Risk Adolescent Parturient: Navigating Anesthetic Management in the Confluence of Nephrotic Syndrome, Diastolic Heart Failure, and Anasarca - Made Bagus Cahya Maha Putra; Tjokorda Gde Agung Senapathi; I Gusti Ngurah Mahaalit Aribawa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Anesthetic management for cesarean delivery in parturients with concurrent nephrotic syndrome and decompensated heart failure presents a profound clinical challenge. Severe anasarca can obliterate anatomical landmarks, while complex cardiorenal pathophysiology creates a state of extreme hemodynamic fragility. This case report describes a systematic, ultrasound-guided approach to overcome these obstacles. Case presentation: A 15-year-old primigravida at 33 weeks gestation, with new-onset nephrotic syndrome and decompensated heart failure (NYHA Class III), required an emergency cesarean section. Clinical examination revealed severe anasarca, rendering lumbar spinal landmarks impalpable. A systematic pre-procedural lumbar ultrasound examination was performed using a low-frequency curvilinear transducer. This allowed for precise identification of the L3-L4 interspace and an accurate skin-to-dura depth measurement of 4.6 cm. A single-attempt subarachnoid block was successfully performed with a reduced dose (10 mg) of hyperbaric bupivacaine. An adequate T4 sensory block was achieved for surgery. The patient remained remarkably hemodynamically stable throughout the procedure, with no episodes of hypotension requiring vasopressor support. A healthy infant was delivered, and both maternal and neonatal outcomes were excellent. Conclusion: This case demonstrates that a systematic pre-procedural ultrasound protocol is an indispensable tool for enhancing the safety and success of neuraxial anesthesia in high-risk obstetric patients. By enabling precise anatomical localization and informed dose reduction, it mitigates procedural risk and supports hemodynamic stability in the face of distorted anatomy and severe cardiorenal comorbidities.